Socio demographic profile of pediatric tuberculosis patients of north Gujarat region, India: a cross sectional study - Jani, Yagnavalkya; Sarvaiya, Ankur N.; Thakor, Nilesh (International Journal of Research in Medical Sciences, 2017)
Background: Tuberculosis continues to be one of the most important public health problems worldwide. It infects one third of the world’s population at any point of time. Children are especially vulnerable to the effects of tuberculosis, which is often difficult to diagnose and therefore difficult to treat effectively. Pediatric TB results from failure of TB control in adults. The objective of the study was to study socio demographic profile of pediatric tuberculosis patients. Methods: This cross sectional observational, descriptive epidemiological study was conducted at GMERS medical college and hospital Dharpur-Patan located in north Gujarat during January 2015 to June 2015. The study was conducted among all the 151 pediatric TB patients who were currently under treatment at selected Hospital. Parents of the patient were informed about the purpose of the study and their informed written consent was taken. By interviewing them on the basis of pre-designed and pre tested proforma, socio demographic information was collected. The collected data was analyzed using statistical package for social science (SPSS 17 Trial version). Results: Out of 151 pediatric patients 87 (57.6%) were male. Age range of the children was 1 to 14 years. In our study mean age of children was 8.41±2.86 years. 68 (45.0%) patients were adolescents. 127 (84.1%) patients were from rural area. 63 (41.7%) heads of the family of patients were illiterate. 116 (76.8%) of the patients lived in joint family. 89 (58.9%) patients had kuccha house. Overcrowding was present in 86.7% of the patients. Family history of TB was present in only 23.2 % of the patients. 76.8% of the patients belonged to social IV and V according to modified Prasad’s classification. 105 (69.5%) patients had extra pulmonary TB. Category-1 constituted 125 (82.7%) cases. 3 % patients had HIV infection. Conclusions: Apart from pharmacological treatment, poor housing condition and illiteracy of the parents of these patients need to be addressed.